Investigating the Chemical and Thermal Based Treatment Procedure on the Clinoptilolite to Improve the Physicochemical Properties - Ezgi BAYRAKDAR ATEŞ (Journal of the Turkish Chemical Society Section B: Chemical Engineering, 2022)
Natural clinoptilolites have been preferred as promising catalysts and adsorption materials due to their low cost and important properties. However, they struggle with their cationic phases and impurities, weakening the physicochemical structure. The main approach is to improve the features of clinoptilolites by applying treatments such as acid modification and calcination. Here in clinoptilolites in two different particle sizes were pre-treated with acid, then, calcined at two different temperatures (300 and 500 °C) with different durations (2 and 3 h). The effects of pre-treatment were investigated with X-ray diffraction (XRD), X-ray fluorescence (XRF), Fourier transform infrared (FTIR), Thermogravimetry (TG-DTG), Differential Thermal Analysis (DTA), N2 adsorption with Brunauer-Emmett-Teller (BET), Scanning Electron Microscopy (SEM) coupled with Energy Dispersion Spectroscopy (EDS) analyses. XRF analysis shows that cations and aluminum were removed due to pre-treatments and that the clinoptilolite, with a smaller particle size, had a higher Si/Al ratio. All clinoptilolites showed good thermal stability up to temperatures 600–800 °C with continuous mass-loss curves. It was determined that surface area and total pore volume increased in most of the samples without agglomeration by SEM-EDS and BET. The surface functional groups were investigated by FTIR and intensities of some bands showed a decrease due to decationization.